2016
DOI: 10.3390/app6120402
|View full text |Cite
|
Sign up to set email alerts
|

A Novel Ropes-Driven Wideband Piezoelectric Vibration Energy Harvester

Abstract: This paper presents a novel piezoelectric vibration energy harvester (PVEH) in which a high-frequency generating beam (HFGB) is driven by an array of low-frequency driving beams (LFDBs) using ropes. Two mechanisms based on frequency upconversion and multimodal harvesting work together to broaden the frequency bandwidth of the proposed vibration energy harvester (VEH). The experimental results show that the output power of generating beam (GB) remains unchanged with the increasing number of driving beams (DBs),… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
11
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
7
1
1

Relationship

1
8

Authors

Journals

citations
Cited by 13 publications
(11 citation statements)
references
References 33 publications
0
11
0
Order By: Relevance
“…One approach consists in exploiting several modes of vibration of the cantilever harvester (making use of segmented electrodes) [14] or of more complex structures, like L-shaped harvesters [15]. Another approach consists in making use of non-linear components like bi-stable cantilevers or ropes [16][17][18]. The possibility of widening the band of the cantilever harvester by increasing the number of degrees of freedom (DOFs) has been analyzed in some research.…”
Section: Introductionmentioning
confidence: 99%
“…One approach consists in exploiting several modes of vibration of the cantilever harvester (making use of segmented electrodes) [14] or of more complex structures, like L-shaped harvesters [15]. Another approach consists in making use of non-linear components like bi-stable cantilevers or ropes [16][17][18]. The possibility of widening the band of the cantilever harvester by increasing the number of degrees of freedom (DOFs) has been analyzed in some research.…”
Section: Introductionmentioning
confidence: 99%
“…The operating bandwidth is extended from 12 to 26 Hz and the power density of the device is significantly improved. Zhang et al 327 reported a novel rope-driven FUC approach, in which the high-frequency generating beam is driven by an array of low-frequency driving beams using ropes. The mechanism takes the advantages of FUC and multimodal harvesting techniques, which not only produces high output power but also has the potential to achieve unlimitedly wide bandwidth with the increasing number of beams.…”
Section: Mechanical Impact Approachmentioning
confidence: 99%
“…Hence, we proposed a low-frequency and wideband harvester based on a hybrid frequency up-conversion (FUC) nonlinear and multimodal mechanism in our previous work [ 57 ], aiming to combine the advantages of these two mechanisms, as demonstrated in Figure 1 . The proposed wideband PVEH system (shown in Figure 1 a) is composed of one high-frequency beam attached with piezoelectric material as the generating beam (HFGB) and multiple low-frequency beams with different frequencies as driving beams (LFDBs).…”
Section: Introductionmentioning
confidence: 99%
“…The main advantages of the rope-driven PVEH can be described as below: Wider or even unlimited bandwidth could be achieved if the number of LFDBs are continuously increased. Unlike wideband PVEH based on an array piezoelectric beams in serial/parallel connection, the output performance of proposed PVEH will not deteriorate with the changing number of LFDBs, which has theoretically and experimentally been proved, and Figure 1 b,c show a typical experimental result [ 57 ]. Similar to the impact-driven FUC wideband PVEH using a stopper, when an individual LFDB pulls the HFGB to oscillate it can achieve wideband energy harvesting, named as rope-driven FUC mechanism.…”
Section: Introductionmentioning
confidence: 99%